CROSS-LINGUISTIC ISSUES IN AVIATION TERMINOLOGY: ENGLISH-BASED TERMS IN OTHER LANGUAGES - Ra’no Ergashova Turayevna (Western European Studies, 2025)
Aviation operates as a highly globalized and safety-critical domain in which professional communication relies on standardized terminology. Due to the dominant role of English as the international language of aviation, a significant proportion of aviation terminology originates in English and is subsequently adopted by other languages. This process, however, raises a number of cross-linguistic issues related to equivalence, semantic precision, and terminological consistency. The present study examines English-based aviation terms as they are integrated into other languages, focusing on linguistic adaptation strategies such as borrowing, calquing, transliteration, and semantic narrowing. Using a qualitative, comparative approach, the paper analyzes selected aviation terms to identify common patterns of cross-linguistic variation and potential risks associated with partial equivalence and semantic shift. The findings suggest that while English-based terminology facilitates international standardization, its adaptation into national languages may generate conceptual asymmetries that affect professional communication. The study contributes to aviation terminology research by highlighting the need for concept-oriented approaches in multilingual contexts and offers practical implications for translation, training, and terminology management in aviation.
Keywords: aviation terminology; cross-linguistic issues; English-based terms; multilingual communication